The scourge of sexual violence in West Africa, unveiled - (:unkn) unknown (My University, 2022)
When Zougba's husband fled the jihadist violence crippling Burkina Faso, she soon found herself with her young son, daughter and other women on the road in a mission to join him. After 10km, four armed men surged into view from the side of the road. Her children bore witness as the men raped her, one after another. The police arrived too late. More than 40% of women in West Africa are victims of violence at least once in their lifetimes, according to a 2018 report, Réseau des Femmes Elues Locales d'Afrique (REFELA). Together with Central Africa (65% of women are victims of violence), these two regions constitute the part of the world with the highest level of violence against women (REFELA 2018 report).
Keywords: African Research